Seaweed as an alternative protein source: Prospective protein extraction technologies - de Souza Celente, Gleison; Sui, Yixing; Acharya, Parag (Innovative food science & emerging technologies, 2023)
Demand for food production has increased due to population growth. The negative environmental impact of animal agriculture necessitates the search for alternatives to animal protein-based products. Potential health benefits from micronutrient-rich seaweeds have attracted significant attention for further research. This encourages the use of seaweed as an alternative protein-rich source. However, traditional seaweed protein extraction presents drawbacks because of energy and water-intensive treatments and poor extraction yield, which limit their application. There is an urge for cost-effective, novel, and sustainable technologies for seaweed protein extraction at the right techno-economics. Thus, this review article discusses the economic potential of seaweed proteins and identifies the traditional technologies applied to extract seaweed protein and their limitations. A detailed analysis of novel methods that could potentially be utilized to extract and enrich seaweed protein is presented. Various protein quantification/qualification approaches reported in the literature have been thoroughly assessed to compare their advantages and disadvantages. Technologies like the pulsed electric field, ultrasound- and microwave-assisted extraction, high-pressure processing, and subcritical-water extraction have huge potential to extract protein from seaweed sustainably yet are relatively under-explored. More research is required to develop further insights on the process-quality inter-relationship of these technologies for improved seaweed protein extraction. Essential amino acid index, protein digestibility corrected amino acid score, and digestible indispensable amino acid score are the best approaches to evaluate seaweed protein quality for human consumption. However, reported studies have barely covered these aspects, including seaweed protein's sensorial quality. •Alternative protein and sustainable protein shift•Eco-innovative protein extraction•Cell disruption and protein isolation•Seaweed protein quantification•Food processing and novel technologies